FACTORES DE RIESGO CLASICOS ASOCIADOS A LA ENFERMEDAD CORONARIA SEVERA. UN ESTUDIO DE CASOS Y CONTROLES ARGENTINO - Olavegogeascoechea, Pablo A.; Urdiales, Pedro L.; Schroeder, Alejandro; Cross, Alejandro LÃ³pez; Cari, MartÃn; GarcÃa, Pablo A. (European Scientific Journal, ESJ, 2014)
Studies showing the relationship between vascular risk factors with severity of coronary disease have mixed results. The aim of this study was to find out evidence regarding the relation aforementioned. This was a casecontrol study. We included patients consecutively admitted to the Angiology Department for unstable angina between January 2006 and June 2010. Those showed stenosis > 70 % stenosis in two or more of epicardial vessels were considered â€œcasesâ€ and controls were selected in 1:1 proportion and they should have had no more than 1-vessel disease (stenosis > 70 % and in the remaining epicardial vessel the stenosis should not be greater than 50 %). The mean age of cases was 62.26 years (95% CI 60.57 % -63.95 %). The case group had presence of hypertension, positive family history and hypercholesterolemia in 88.3 %, 76.7 % and 19.4 % respectively, while in the controls was there were 73.3 %, 60.4 % and 13.9 % respectively. The presence of diabetes was significantly higher in cases tan in controls, 36.9 % vs. 11.9 % (p = 0.0001) and the association between hypertension and family history coronary disease also showed significant association (p = 0.001). In our study the presence of diabetes mellitus in a strong predictor of severe coronary disease and the presence of hypertension alone or in associated with a family history of coronary disease were independent predictors of severe coronary disease.